Does Levosimendan hasten veno-arterial ECMO weaning? A propensity score matching analysis - Nicolas Paulo; Antoine Kimmoun; David Hajage; Pierre Hubert; David Levy; Marc Pineton de Chambrun; Juliette Chommeloux; Ouriel Saura; Grégoire Del Marmol; Quentin Moyon; Guillaume Hékimian; Melchior Gautier; et al. (Annals of Intensive Care)
Abstract Background Preliminary evidence from small, single-center studies suggests levosimendan may improve the likelihood of successful venoarterial extracorporeal membrane oxygenation (VA-ECMO) weaning in patients with cardiogenic shock. However, the literature is limited and presents conflicting results. We aimed to assess the benefits of levosimendan on VA-ECMO for time to successful ECMO weaning, using a pragmatic and rigorous definition of successful VA-ECMO weaning in patients with potential for cardiac function recovery. Methods A retrospective bicentric study over 6 years was conducted, including patients who received levosimendan during their ECMO course. Patients with post-cardiotomy cardiogenic shock or end-stage chronic heart failure were excluded. Patients receiving levosimendan while on VA-ECMO were matched to those not receiving levosimendan during the same period, based on pre-specified variables and time from ECMO initiation. The primary endpoint was successful VA-ECMO weaning, defined as survival without death, heart transplantation, or LVAD within 30 days after VA-ECMO withdrawal. Results Over the study period, 320 patients treated with VA-ECMO for refractory cardiogenic shock were included, of whom 68 received levosimendan during their ECMO course. Propensity score matching yielded 47 unique pairs of patients with comparable characteristics. After matching, successful ECMO weaning was achieved in 16 out of 47 patients (34%) in the no-levosimendan group and 21 out of 47 patients (45%) in the levosimendan group (sHR, 1.45 [95% CI, 0.77–2.70]; P = 0.25). Similarly, there were no significant differences between the groups in terms of bridge-to-heart transplant, LVAD, or death. Left ventricular ejection fraction and aortic velocity time integral improved significantly after levosimendan in all patients, regardless of their VA-ECMO weaning status. Conclusion In patients with non-postoperative cardiogenic shock supported by peripheral VA-ECMO, levosimendan was not associated with increased rates of successful VA-ECMO weaning or improved 30-day and 6-month bridge-free survival. Results from double-blinded randomized controlled trials are urgently needed to clarify the effectiveness and optimal timing of levosimendan in this specific population.